2020
DOI: 10.1161/hypertensionaha.119.13649
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Blood Pressure in Relation to Plasma and Urinary Manganese

Abstract: The association of blood pressure (BP) with manganese, an essential trace element required for human health, remains poorly studied. In 734 randomly recruited Swiss participants (mean age, 47.5 years; 51.4% women), we related ambulatory BP to two biomarkers, plasma manganese (pMn) and the urinary manganese excretion (uMn). To allow for diurnal variation, we assessed BP and uMn over 24-h and during wakefulness and sleep, using split urine samples. 24-h, day-and night-time systolic/diastolic BPs averaged 119.8/7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The possible mechanisms of cardiovascular toxicity induced by Mn include changes in autonomic nerve function, Ca 2+ channel obstruction, myocardial mitochondrial damage, reduction of dopamine and 5-hydroxytryptophane, interference with cholinesterase synthesis, and reduction of superoxide dismutase activity ( 228 ). In addition, there were positive associations between diastolic blood pressure and plasma Mn over 24 hours and during daytime and between systolic blood pressure and urinary Mn at night ( 229 ).…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanisms of cardiovascular toxicity induced by Mn include changes in autonomic nerve function, Ca 2+ channel obstruction, myocardial mitochondrial damage, reduction of dopamine and 5-hydroxytryptophane, interference with cholinesterase synthesis, and reduction of superoxide dismutase activity ( 228 ). In addition, there were positive associations between diastolic blood pressure and plasma Mn over 24 hours and during daytime and between systolic blood pressure and urinary Mn at night ( 229 ).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies reported an inverse association of Se and BP (Nawrot et al 2007;Salonen et al 1988), but an analysis of the NHANES 2003-2004 data found that higher serum Se levels were associated with a higher prevalence of hypertension in U.S. adults (Laclaustra et al 2009). For Mn, an analysis of the U.S. NHANES 2011-2014 data found that higher urinary Mn levels were associated with lower BP in adults (Wu et al 2017), whereas another study in Swiss adults found a positive association of plasma and urine Mn with BP (Zhang et al 2020a). It should also be noted that many previous studies did not examine (and thus may have missed) the possible nonlinear associations of these two elements with BP.…”
Section: Mn and Sementioning
confidence: 99%
“…It is also possible that nutrients such as manganese is involved in the mechanisms. Prior study found that both SBP and DBP were associated with manganese levels in the body, 46 whereas higher levels of manganese‐dependent enzyme were correlated with increased antioxidant activity in oxidative stress conditions, 47 possibly leading to elevated risk of VTE. More experimental studies are warranted to underline the potential mechanisms.…”
Section: Discussionmentioning
confidence: 99%